Using imaging to study inflammatory platelet–leukocyte interactions in vivo. (3rd July 2020) - Susanto, Olivia; Hickey, Michael J.
Abstract: In addition to their roles in hemostasis and thrombosis, platelets are now recognized as making important contributions to a wide variety of inflammatory responses. This function primarily occurs as a result of intravascular interactions of platelets with leukocytes undergoing recruitment to the site of inflammation. As these interactions occur under the shear forces of flowing blood, they are typically rapid and highly dynamic. As such, the use of rapid frame-rate forms of in vivo microscopy, such as spinning-disk confocal intravital microscopy, have emerged as the optimal approaches for investigating these interactions and delineating their molecular basis and contribution to the inflammatory response. In this review, we provide an overview of the different methodologies employed to image platelet–leukocyte interactions in vivo, and examine the contributions of these interactions to inflammation that have been uncovered by intravital imaging.